Visual Outcome Following Intra-vitreal Bevacizumab Injection in Neovascular Age-related Macular Degeneration - Azfar N. Hanfi, P. S. Mahar (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess the visual outcome after intravitreal Bevacizumab (Avastin) injection in eyes with choroidal neovascularization due to age–related macular degeneration (ARMD). Material and Methods: This study was conducted in Isra Post-graduate Institute of Ophthalmology / Al-Ibrahim Eye Hospital, Karachi from February 2007 to January 2008. Forty – two eyes of 30 patients with neovascular ARMD received 3 intravitreal injections of Bevacizumab (1.25 mg / 0.05 ml) at 4-weeks interval and were followed up for 12 weeks after the initial treatment. Best – corrected visual acuity (BCVA), complete ophthalmic examination, and fluorescein angiography were done at baseline and on follow up visits. Main outcome measures were changes in Snellen’s acuity, and change in angiographic characteristics of the lesions. Results: The mean age ± SD of patients was 65.33 ± 8.32 years. The mean BCVA ± SD at baseline was 20/178 ± 4.6 lines on Snellen’s quotations which improved to 20/142 ± 4.9 lines and 20/138 ± 4.9 lines at 4 and 12 weeks, respectively (p<0.001). Visual acuity (VA) improved or remained stable in thirtyseven (88%) eyes. Improvement of 1 or more lines was seen in 17 (40%) eyes. In majority of the patients, fluorescein angiography showed decreased leakage and regression of choroidal neovascularization (CNV). No patient had severe vision loss or significant ocular or systemic side effects. Conclusion: Intravitreal Bevacizumab injection is effective in improving and stabilizing the visual acuity in patients with neovascular ARMD.